Diazinon-induced Cognitive Impairment: Alternations in Amyloid Precursor Proteins, and TNF-α Expression in the Hippocampus of Adult Rats - Sarailoo, Mehdi; Afshari, Salva; Asghariazar, Vahid; Niri, Mehdi Vosoughi; Safarzadeh, Elham; Dadkhah, Masoomeh (Current Topics in Medicinal Chemistry, 2025)
BackgroundOrganophosphate pesticides such as diazinon (DZN) are involved in developing psychological symptoms and memory deficits, but their effects on the amyloid precursor proteins (APP) gene expression remain unclear.Materials and MethodsFollowing low-level oral exposure to the DZN (2 mg/kg), we used novel object recognition, open field, and elevated plus-mazes (EPM) to assess memory and anxiety-like behaviors in rats. We also evaluated alteration in the levels of tumor necrosis factor (TNF-α), amyloid precursor protein (APP), APP-like protein-2 (APLP2), and amyloid-β (Aβ) via western blotting and ELISA. Real-time quantitative PCR was performed to evaluate the expression of the related genes in the hippocampus.ResultsThe findings demonstrated that whereas DZN exposure boosted anxiety-like behaviors at any exposure level, only prolonged exposure (12 weeks) resulted in memory impairment. The study also found that the hippocampal expression of APP and APLP2 decreased after 12 weeks of exposure but not after 5 days. Additionally, Aβ increased after long-lasting exposure to DZN, indicating the APP contribution to AD pathologies. The TNF-α gene was up-regulated following 5 days of exposure, but 12 weeks had no effect.ConclusionOur finding demonstrates that long-lasting exposure to low levels of DZN in adulthood stimulates APP degradation, possibly contributing to poor cognitive outcomes.
Keywords: TNF-α